How Reclamation Policy Shapes China’s Coastal Wetland Ecosystem Services - Yuefei Zhuo; Tiantian Li; Zhongguo Xu; Guan Li (Systems)
China’s reclamation regulation policy is an important policy tool used by the government to balance land development and ecological protection in coastal areas, but few studies have focused on the impact of the implementation of this policy on ecosystem services. To fill the gap, this study takes Ningbo City as an example, applies the InVEST model as a scenario analysis and trend indication tool, combines the market value method to quantify the ecosystem services of coastal wetlands, and explores the impact of the reclamation regulation policy on the coastal wetland ecosystem services through the regression discontinuity model. The findings are as follows: (1) from 2005 to 2020, the natural ecological landscape in the coastal zone of Ningbo City continued to shrink, but the overall value of ecosystem services showed a fluctuating upward trend. Among them, cropland and wetlands served as the primary conduits for ecosystem services in this region, highlighting the need to strengthen the protection of these two land types. (2) The implementation of reclamation regulation policy has an impact on ecosystem services. The policy implementation in 2011 appeared to suppress the downward trend of ecological habitat quality and carbon storage, while the policy implementation in 2017 had a positive impact on the enhancement of carbon storage and material production. (3) As for the effect of reclamation regulation policy on the changes in ecosystem services, although the measured positive impact of reclamation regulation policy on ecological habitat quality was less statistically pronounced compared to other services during the study period, it had significant positive effects on carbon storage and material production. On the whole, the reclamation regulation policy proves effective in contributing to the maintenance of coastal wetland ecosystem services. Although the model-based results in this study reveal more indicator trends rather than precise quantitative evidence, it helps mitigate degradation trends and enhance specific services like carbon storage and material production. Through its implementation, the policy aids in pursuing the win–win goal of balancing urban economic development and ecological environment protection.